A data-driven algorithm to predict throughput bottlenecks in a production system based on active periods of the machines. (November 2018) - Subramaniyan, Mukund; Skoogh, Anders; Salomonsson, Hans; Bangalore, Pramod; Bokrantz, Jon
Graphical abstract: Highlights: Proposes a MES based data-driven algorithm to predict throughput bottlenecks. Devised an approach to determine the size historical machine data to predict bottlenecks. Proposes an evaluation framework to evaluate the algorithm performance. Compared the performance of the algorithm with naïve bottleneck prediction method. Proposed algorithm outperformed naïve method of bottleneck prediction. Abstract: Smart manufacturing is reshaping the manufacturing industry by boosting the integration of information and communication technologies and manufacturing process. As a result, manufacturing companies generate large volumes of machine data which can be potentially used to make data-driven operational decisions using informative computerized algorithms. In the manufacturing domain, it is well-known that the productivity of a production line is constrained by throughput bottlenecks. The operational dynamics of the production system causes the bottlenecks to shift among the production resources between the production runs. Therefore, prediction of the throughput bottlenecks of future production runs allows the production and maintenance engineers to proactively plan for resources to effectively manage the bottlenecks and achieve higher throughput. This paper proposes an active period based data-driven algorithm to predict throughput bottlenecks in the production system for the future production run from the large sets of machine data. To facilitate the prediction, we employ an auto-regressive integrated moving average (ARIMA) method to predict the active periods of the machine. The novelty of the work is the integration of ARIMA methodology with the data-driven active period technique to develop a bottleneck prediction algorithm. The proposed prediction algorithm is tested on real-world production data from an automotive production line. The bottleneck prediction algorithm is evaluated by treating it as a binary classifier problem and adapted the appropriate evaluation metrics. Furthermore, an attempt is made to determine the amount of past data needed for better forecasting the active periods.